2022
DOI: 10.1101/2022.01.31.478585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Striatal dopamine encodes the relationship between actions and reward

Abstract: Despite the well described role of dopamine in the striatum for motor learning and movement, its function in encoding actions and their outcomes for goal-directed action is less clear. Here, rats acquired two actions for distinct outcomes while we simultaneously recorded dopamine release in the dorsomedial striatum as these action-outcome associations were incremented and selectively degraded. Goal-directed actions generated a lateralized dopamine signal that reflected the strength of the action-outcome associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…In non-stressful conditions, this asymmetry is associated with motor functions such as spatial preferences, direction of rotation or pressing a lever on a particular side of an instrumental apparatus [8, 19, 20], and can be presented as either left or the right dominance, depending on which limb is used or the direction of the motor movement. The functional significance of the asymmetry is not limited to motor movement; an asymmetrical increase in DA associated with directional movement also facilitates the learning associated with that action [21]. Following stress, we have found different patterns of asymmetry in DA activity in the dorsal striatum following the three different types of stress used.…”
Section: Discussionmentioning
confidence: 93%
“…In non-stressful conditions, this asymmetry is associated with motor functions such as spatial preferences, direction of rotation or pressing a lever on a particular side of an instrumental apparatus [8, 19, 20], and can be presented as either left or the right dominance, depending on which limb is used or the direction of the motor movement. The functional significance of the asymmetry is not limited to motor movement; an asymmetrical increase in DA associated with directional movement also facilitates the learning associated with that action [21]. Following stress, we have found different patterns of asymmetry in DA activity in the dorsal striatum following the three different types of stress used.…”
Section: Discussionmentioning
confidence: 93%
“…Motivated behavior is driven by the ability to derive value from the outcome of an action. The nigrostriatal circuit, whereby SNc neurons release dopamine onto DS neurons, is essential for modulating acquisition and updating motivated behaviors 66, 67 , including the motivation to eat 21 . We and others have demonstrated that the presence of nutrients in the gut evokes dopamine release in the dorsal striatum.…”
Section: Discussionmentioning
confidence: 99%